FACTORS AFFECTING SUSTAINABLE GROWTH OF SUSTAINABLE INVESTMENT GROUP IN THE STOCK EXCHANGE OF THAILAND - อมาตยกุล, ขนิษฐา; Pongsupatt, Tharinee; Pongsupatt, Apichat (Journal of Buddhist Education and Research (JBER), 2021)
The purpose of this study was to explore factors affecting sustainable growth of Sustainable Investment Group in the Stock Exchange of Thailand. In this study the secondary cross - sectional data and time series of 76 companies listed on the Stock Exchange of Thailand was collected. This study examined six independent variables including current ratio, total asset turnover, profitability, debt to equity ratio, dividend payout ratio, and firm size. This data was analyzed by the Panel Least Squares Method, Fixed Effect Regression Model (FEM) on a quarterly basis starting from the first quarter of 2016 to the 4th quarter of 2020, entirely the 5 years period 20 quarters. The total amount of data was 1,520. The results showed that information factor affecting the sustainable growth of listed companies with positively statistical significance level of 0.05 was profitability (ROA). Meanwhile, the debt-to-equity ratio (D/E) and dividend payout ratio (DPR) had negative correlation to sustainable growth with an R-Square of 0.4048.